Germplasm, Breeding, and Genomics in Potato Improvement of Biotic and Abiotic Stresses Tolerance - Tiwari, Jagesh Kumar; Buckseth, Tanuja; Zinta, Rasna; Bhatia, Nisha; Dalamu, Dalamu; Naik, Sharmistha; Poonia, Anuj K.; Kardile, Hemant B.; Challam, Clarissa; Singh, Rajesh K.; Luthra, Satish K.; Kumar, Vinod; et al. (Frontiers in Plant Science, 2022)
Potato is one of the most important food crops in the world. Late blight, viruses, soil and tuber-borne diseases, insect-pests mainly aphids, whiteflies, and potato tuber moths are the major biotic stresses affecting potato production. Potato is an irrigated and highly fertilizer-responsive crop, and therefore, heat, drought, and nutrient stresses are the key abiotic stresses. The genus Solanum is a reservoir of genetic diversity, however, a little fraction of total diversity has been utilized in potato breeding. The conventional breeding has contributed significantly to the development of potato varieties. In recent years, a tremendous progress has been achieved in the sequencing technologies from short-reads to long-reads sequence data, genomes of Solanum species (i.e., pan-genomics), bioinformatics and multi-omics platforms such as genomics, transcriptomics, proteomics, metabolomics, ionomics, and phenomics. As such, genome editing has been extensively explored as a next-generation breeding tool. With the available high-throughput genotyping facilities and tetraploid allele calling softwares, genomic selection would be a reality in potato in the near future. This mini-review covers an update on germplasm, breeding, and genomics in potato improvement for biotic and abiotic stress tolerance.